The movement from «chaos to order» in the process of language evolution - Shaibakova Д.Д.; Zhaparova* Т.Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article considers the development of a language in which, as well as in an open system, chaos is established and its further ordering takes place. New elements that enter the language are adapted in it, the rules and behavior in the language change. In this case, such a process is viewed from the standpoint of synergetics, which shows that in an open environment, the collision of energy and matter creates chaos, which should strive for order. An attempt has been made to understand how the correlation of chaos and order is resolved in a communicative environment. The relevance of the topic lies on the analysis of new models of word formation in speech, linguistic changes resulting from the interaction of factors of external and internal order. Chaos and ordering of movements in the language, control of a complex, self-organizing, dynamic system allow tracing the impact on the communicative environment and the ability to prevent the appearance of deviations in the language.